2005
DOI: 10.2176/nmc.45.464
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging of Traumatic Subdural Hematoma in the Subacute Stage-Five Case Reports-

Abstract: Five cases of traumatic subdural hematomas in the subacute stage (from 7 to 20 days after head injury) were treated in one male and four females, aged from 63 to 82 years, with evacuation via craniotomy in three and aspiration via burr hole surgery in two. All hematomas were evaluated by T 1 -, T 2 -, and diffusion-weighted magnetic resonance imaging, and measurement of the apparent diffusion coefficient (ADC). Diffusion-weighted imaging showed the hematoma as a crescent high intensity area with a low intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…5,12) Therefore, the majority of reported clinical studies of SASDH have been conducted in Japan. 1,3,6,9,10,[13][14][15] SASDH has been reported to occur in approximately 10% of ASDH cases treated conservatively. 1,14) In the Subdural Hematoma Removal in the Subacute or Chronic Stage present study, SASDH was found in 7 (18.4%) of 38 patients, indicating that it is not uncommon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,12) Therefore, the majority of reported clinical studies of SASDH have been conducted in Japan. 1,3,6,9,10,[13][14][15] SASDH has been reported to occur in approximately 10% of ASDH cases treated conservatively. 1,14) In the Subdural Hematoma Removal in the Subacute or Chronic Stage present study, SASDH was found in 7 (18.4%) of 38 patients, indicating that it is not uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,6,9,14) These characteristics have included a comparatively thick high-density hematoma in the acute stage, expanding along the skull vault and including low-density components, an enlarged hematoma in the subacute stage showing a change to iso-or low density, a low prevalence of complicating traumatic lesions including brain swelling, and frequent occurrence of brain atrophy. On the other hand, the characteristics of SASDH evident on MR images have included gyrus patterns (a feature indirectly suggesting absence of an inner membrane) 3) on the brain surface side of a hematoma, and a two-layered hematoma structure 6) consisting of a high-intensity component (solid or jelly-like clot) and a low-intensity component (liquid hematoma) on diffusion-weighted MR images. The latter feature in particular has been reported to be useful for diagnosis and surgical decision-making in patients with SASDH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13) Diffusionweighted MR imaging has proved useful in a study of the natural history of ischemic stroke, 15) and is now a promising technique for early detection of cerebral infarction in routine clinical practice. 2,14,19,22) We recently confirmed that diffusion-weighted imaging showed solid clots as high intensity areas in patients with traumatic subacute subdural hematoma 10) and organized subdural hematoma, 11) and measurement of the apparent diffusion coefficient (ADC) values was useful for differentiating solid from liquid components. 11) However, the diffusionweighted imaging appearance of chronic subdural hematomas has been rarely reported, 9) and the potential of diffusion-weighted imaging for the evaluation of chronic subdural hematoma has not yet been established.…”
Section: Introductionmentioning
confidence: 88%
“…5) We recently reported that diffusion-weighted MR imaging can differentiate solid from liquid hematoma in the subacute stage. 9) Here, we discuss the usefulness of diffusion-weighted MR imaging and apparent diffusion coefficient (ADC) values of the organized subdural hematoma.…”
Section: Introductionmentioning
confidence: 99%